Tren Jilbab di kalangan milenial: motivasi pemakaian Jilbab dan pengaruhnya terhadap perilaku sosial keagamaan - Hadikusuma, Riza; Hafiduddin, Hafiduddin; Nurjannah, Darul; Maryono, Maryono (Indonesian Journal of Islamic Religious Education, 2023)
The phenomenon of wearing the hijab among Muslim women in Indonesia has experienced a rapidly increasing trend over the last two decades. The use of the hijab, which was initially only limited to certain circles, has now become a fashion model in almost all circles of society, including students and students. This research aims to explore and photograph the motivation of Jakarta State Polytechnic students to wear the hijab and their social and religious behavior. The objects of this research were Muslim students at the Jakarta State Polytechnic who wore the hijab, with a sample of 100 people. The data collection method uses a questionnaire. The incoming data is processed, analyzed, and presented descriptively. The results of this study show that Muslim female students at the Jakarta State Polytechnic generally wear the hijab more because of intrinsic encouragement than extrinsic encouragement, respectively getting approval levels of 89% and 41%. They also have good religious and social behavior, as shown by an approval level of 80% for religious behavior and 70% for social behavior